2023
DOI: 10.2147/jir.s418345
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavonoids of Rhizoma Drynariae Treat Osteoarthritis by Inhibiting Arachidonic Acid Metabolites Through AMPK/NFκB Pathway

Guang-Yao Chen,
Xiao-Yu Liu,
Xue-Er Yan
et al.

Abstract: Previous clinical studies have found that total flavonoids of Rhizoma Drynariae (TFRD) have a good therapeutic effect on osteoarthritis (OA), but its therapeutic mechanism needs further research. Methods: OA rat model was established by Hulth method and was intervened by TFRD. Pathological assessments were conducted to assess the protective effect of TFRD on cartilage. Serum metabolomics and network pharmacology were detected to predict the mechanism of TFRD treating OA. In further experiments, molecular biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It was already demonstrated that their beneficial effect on osteoarthritis, urinary tract infections in children, and due to their antiangiogenic and anticancer activities, proanthocyanidins could be used as an antitumor agent under various signaling pathways, participating in cell survival, apoptosis, migration, and invasion. [41][42][43] There are studies in the literature that demonstrate the favorable effect of proanthocyanidins in the treatment of hemangiomas, although the beneficial role of these substances in conditions involving the proliferation of vascular endothelial cells and uncontrolled angiogenesis has already been demonstrated. 37,38,42 Proanthocyanidins bind to VEGF and inhibit HIF-1α translation; the decrease of VEGF expression through mediating the PI3K/Akt and mTOR/p70S6K signaling pathways arrests the proliferation, invasion, and metastasis of tumor cell.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…It was already demonstrated that their beneficial effect on osteoarthritis, urinary tract infections in children, and due to their antiangiogenic and anticancer activities, proanthocyanidins could be used as an antitumor agent under various signaling pathways, participating in cell survival, apoptosis, migration, and invasion. [41][42][43] There are studies in the literature that demonstrate the favorable effect of proanthocyanidins in the treatment of hemangiomas, although the beneficial role of these substances in conditions involving the proliferation of vascular endothelial cells and uncontrolled angiogenesis has already been demonstrated. 37,38,42 Proanthocyanidins bind to VEGF and inhibit HIF-1α translation; the decrease of VEGF expression through mediating the PI3K/Akt and mTOR/p70S6K signaling pathways arrests the proliferation, invasion, and metastasis of tumor cell.…”
Section: Dovepressmentioning
confidence: 99%
“…[41][42][43] There are studies in the literature that demonstrate the favorable effect of proanthocyanidins in the treatment of hemangiomas, although the beneficial role of these substances in conditions involving the proliferation of vascular endothelial cells and uncontrolled angiogenesis has already been demonstrated. 37,38,42 Proanthocyanidins bind to VEGF and inhibit HIF-1α translation; the decrease of VEGF expression through mediating the PI3K/Akt and mTOR/p70S6K signaling pathways arrests the proliferation, invasion, and metastasis of tumor cell. This may be the process of proanthocyanidin controlling hemangioma growth.…”
Section: Dovepressmentioning
confidence: 99%